Paul Ricoeur, leitor de Rawls: filosofia da religião e o sentido da justiça - Cordeiro Neto, Manoel Botelho (2020)
This present work aims to introduce the Philosophy of Religion in Paul Ricoeur from the dialectical tension existing in the relationship between justice and love. To this end, it will be necessary to understand the structure of Ricoeurian philosophical thought, its theory of metaphor, its philosophical hermeneutics and its anthropology. In addition, Rawls' influence on the elaboration of the concept of justice in Ricoeur will also be investigated. Justice and love are two topics widely discussed not only in academia, but also in everyday language. The discussion about justice, the different conceptions, principles, theories, and its meaning is as contemporary as it takes us to different thinkers like Aristotle in the 4th century before the common era. John Rawls who seeks to develop a Theory of Justice as Fairness is Paul Ricoeur's main source in the development of his theory of justice. Ricoeur uses Rawls as an inspiration for foundation and questioning demonstrating the ethical assumptions of the Rawlsian procedure. In doing so Ricoeur meets his own Philosophy of Religion, especially in the question of the commandment of love and its relationship with the principles of justice and the Golden Rule. This work aims to present Ricoeur's philosophical perspective on love and justice based on religion and law in order to present Ricoeur's Philosophy of Religion, in these terms